2022
DOI: 10.1111/lam.13711
|View full text |Cite
|
Sign up to set email alerts
|

Oxacillinases and antimicrobial susceptibility of Ralstonia pickettii from pharmaceutical water systems in Croatia

Abstract: This study evaluated antibiotic susceptibility and presence of blaOXA22 and blaOXA60 genes in 81 isolates of Ralstonia pickettii obtained from different purified and ultra‐pure water systems in two different geographical areas of Croatia. E‐test and disc diffusion test were performed to determine antibiotic susceptibility. Polymerase chain reaction was applied to detect genes encoding OXA‐22 and OXA‐60 oxacillinases previously identified in R. pickettii. The isolates were genotyped by pulsed‐field gel electrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
0
2
1
Order By: Relevance
“…Our isolated strain was resistant to tobramycin; this finding was consistent with the results of Yan Tao et al [ 1 ], but inconsistent with those reported by Monica Basso et al [ 4 ]. Moreover, our isolated strain was resistant to meropenem; this observation differed from the results reported in the literature, except for the study of Monica Basso et al Differences were also found in sensitivity to other antibiotics, particularly carbapenems and aminoglycosides, which might be due to the presence of two inducible β-lactamases, namely blaOXA-22 and blaOXA-60 [ 14 ]. The existence of these beta lactamases require further studies to verify in the isolated strain.…”
Section: Discussioncontrasting
confidence: 85%
“…Our isolated strain was resistant to tobramycin; this finding was consistent with the results of Yan Tao et al [ 1 ], but inconsistent with those reported by Monica Basso et al [ 4 ]. Moreover, our isolated strain was resistant to meropenem; this observation differed from the results reported in the literature, except for the study of Monica Basso et al Differences were also found in sensitivity to other antibiotics, particularly carbapenems and aminoglycosides, which might be due to the presence of two inducible β-lactamases, namely blaOXA-22 and blaOXA-60 [ 14 ]. The existence of these beta lactamases require further studies to verify in the isolated strain.…”
Section: Discussioncontrasting
confidence: 85%
“…Additionally, it is capable of producing the chromosomal beta-lactamase OXA-60 that hydrolyzes imipenem. 16,17 OXA-22 and OXA-60 beta lactamases have been recently reported in environmental strains of Ralstonia. 17 To our knowledge, this is the first 2).…”
Section: Discussionmentioning
confidence: 99%
“…16,17 OXA-22 and OXA-60 beta lactamases have been recently reported in environmental strains of Ralstonia. 17 To our knowledge, this is the first 2). This can impose a pending threat of hospital associated infections by the organism that are hard to treat since Ralstonia spp.…”
Section: Discussionmentioning
confidence: 99%